A flexible specification model based on XML for parallel applications - Enomoto, C.; Henriques, M. A. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
This article introduces a new workflow specification model for parallel applications. Many parallel systems allow only the following basic flow control: (1) a coordinator task distributes the data among the worker tasks, (2) the worker tasks process the data in parallel and (3) the coordinator task gather all the results. In some systems the application execution flow is based on a dependence relationship among tasks, representing a directed acyclic graph (DAG). Even with this model, it is not possible to execute some important parallel applications and, therefore, there is a need for a new specification model with more sophisticated flow controls that allow, for example, conditional branching and iterations at the level of task management. The purpose of this article is to present a proposal for a new parallel application specification model that provides new types of control structures and allows the implementation of a broader range of applications.